Benefit of Whole Pelvic Radiotherapy Combined with Neoadjuvant Androgen Deprivation for the High-Risk Prostate Cancer. (14th September 2009) - Milecki, Piotr; Baczyk, Maciej; Skowronek, Janusz; Antczak, Andrzej; Kwias, Zbigniew; Martenka, Piotr
Abstract : Aim . To study whether use of neoadjuvant androgen deprivation therapy (N-ADT) combined with whole pelvic radiotherapy (WPRT) for high-risk prostate cancer patients was associated with survival benefit over prostate radiotherapy (PORT) only. Material and Methods . Between 1999 and 2004, 162 high-risk prostate cancer patients were treated with radiotherapy combined with long-term androgen deprivation therapy (L-ADT). Patients were prospectively assigned into two groups: A (N-ADT + WPRT + L-ADT)n = 70 pts, B (PORT + L-ADT)n = 92 pts. Results . The 5-year actuarial overall survival (OS) rates were 89% for A and 78% for B (P = .13). The 5-year actuarial cause specific survival (CSS) rates were A = 90% and B = 79% (P = .01). Biochemical progression-free survival (bPFS) rates were 52% versus 40% (P = .07), for groups A and B, respectively. Conclusions . The WPRT combined with N-ADT compared to PORT for high-risk patients resulted in improvement in CSS and bPFS; however no OS benefit was observed.